Lovastatin analogues and other metabolites from soil-derived Aspergillus terreus YIM PH30711. (January 2018) - Wang, Qiang; Yang, Ya-Bin; Yang, Xue-Qiong; Miao, Cui-Ping; Li, Yi-Qing; Liu, Shi-Xi; Luo, Na; Ding, Zhong-Tao; Zhao, Li-Xing
Abstract: Eight previously undescribed metabolites including of lovastatin analogues, a pair of diastereoisomers, a cyclopentenone dimer, and three polyketides were isolated from the culture of Aspergillus terreus YIM PH30711. Two types of unprecedented skeletons, benzene-cyclopentanone complex and linear polyketide, and an unusual dimer structure were determined by spectral analysis. Compound, 3α-hydroxy-3, 5-dihydromonacolin L showed moderate activity against HMG-CoA reductase, with an inhibition ratio of 34% at the concentration of 50 μM, while lovastatin and dihydromonacolin K ethyl ester presented much stronger activity against HMGR with inhibition rates of 85% and 90% at the concentration of 50 μM, respectively. Aspereusin A was active against AChE with a ratio of 62% at the concentration of 50 μM, while its stereomers did not showed obvious inhibition (<10%). The configuration at C-4 of these three diastereoisomers was crucial in the inhibition against AChE, and the β -orientation of substituted methoxyl acrylic acid should be beneficial to the combining with AChE. Graphical abstract: Two types of unprecedented skeletons, benzene-cyclopentanone complex and linear polyketide and an unusual dimer structure were found, some compounds showed moderate activities against HMG-CoA reductase and AChE. Image 1 Highlights: Eight previously undescribed compounds were isolated from Aspergillus terreus. Two types of undescribed skeletons, and an unusual dimer structure were found. Some compounds showed inhibitions against HMGR and AChE. The configuration at C-4 of aspereusin A was crucial in the inhibition against AChE.